Incorporating social preferences into the ecological limits of hydrologic alteration (ELOHA): a case study in the Yampa‐White River basin, Colorado. (9th June 2015) - Martin, David M.; Labadie, John W.; Poff, N. LeRoy
Summary River management involves satisfying societal preferences alongside environmental needs for a healthy river ecosystem. Environmental flows is a discipline that aims to define streamflow requirements that achieve desired social and ecological conditions in rivers. The ecological limits of hydrologic alteration (ELOHA) framework takes a regional approach towards assessing relationships between human‐caused river flow alterations and social–ecological benefits. ELOHA allows for, but does not specify, a social process with practical guidelines for incorporating social preferences into environmental flow management problems. Studies using the ELOHA framework are being performed around the world. This study presents development of a decision support tool to prioritise river basin criteria and to rank river segments in order of combined hydro‐ecological and social environmental flow needs. We integrate this tool with hydro‐ecological components of an ELOHA application in the Yampa–White River basin in north‐west Colorado. Stakeholder preferences were collected with a survey, and the analytic hierarchy process was applied to estimate the importance of five criteria identified as socially valued proxies of freshwater management in the basin. Analytical methods for multicriteria decision analysis were used to integrate the preference information with results from the ELOHA application to prioritise the basin river segments. Our methods and results provide a means to facilitate stakeholder negotiation and future environmental flow policy analyses. By extending the existing ELOHA framework to include a social preference component, this approach is general and can be applied to environmental flow policy and management in other river basins.